Ethylene scavengers for extended freshness: A critical comparison between physisorption and chemistry process - Yanan Wang; Jingfei Xu; Rinat M. Iskakov; Xicheng Jia (Applied Food Research)
This review highlights advancements in ethylene removal technologies tailored for fruit and vegetable (F&V) preservation, with a focus on physical adsorption and chemical elimination methods. Conventional approaches, such as potassium permanganate (KMnO₄) and 1-methylcyclopropene (1-MCP), are limited by toxicity concerns, declining efficiency, and potential fruit disorders. Emerging alternatives, particularly catalytic oxidation using metal oxide catalysts like TiO₂, offer efficient ethylene degradation into non-toxic byproducts. Incorporating these catalysts with porous materials, such as zeolites, enhances ethylene adsorption while providing multifunctional benefits, including antibacterial activity. In addition to discussing the materials of the adsorbents, their binding mechanisms (such as van der Waals forces and π-complexation) were also studied. Future research directions include improving cost-efficiency, optimizing material performance for practical applications, and ensuring food safety in packaging systems. These advancements represent a sustainable strategy to extend the shelf life of F&V in the postharvest supply chain.